2020
DOI: 10.1101/2020.11.03.366757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of nonstructural protein 1 from SARS-CoV-2

Abstract: The periodic emergence of novel coronaviruses (CoVs) represents an ongoing public health concern with significant health and financial burden worldwide. The most recent occurrence originated in the city of Wuhan, China where a novel coronavirus (SARS-CoV-2) emerged causing severe respiratory illness and pneumonia. The continual emergence of novel coronaviruses underscores the importance of developing effective vaccines as well as novel therapeutic options that target either viral functions or host factors recr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 58 publications
1
39
0
Order By: Relevance
“…residues 10 to 127) showed minor backbone divergence when compared to the RefSeq model. Thus, our results are in accordance with Clark et al 18 and Semper et al 22 who analyzed the structure of SARS-CoV-2 NSP1 (10-126aa) and reported that the tertiary structure of NSP1 is composed of regular secondary structural elements that are arranged sequentially as b1-g1-a1-b2-g3-b3-b4-b5-b6-b7, with g1 and g2 being 310 helices.…”
Section: Methodssupporting
confidence: 93%
See 1 more Smart Citation
“…residues 10 to 127) showed minor backbone divergence when compared to the RefSeq model. Thus, our results are in accordance with Clark et al 18 and Semper et al 22 who analyzed the structure of SARS-CoV-2 NSP1 (10-126aa) and reported that the tertiary structure of NSP1 is composed of regular secondary structural elements that are arranged sequentially as b1-g1-a1-b2-g3-b3-b4-b5-b6-b7, with g1 and g2 being 310 helices.…”
Section: Methodssupporting
confidence: 93%
“…The RMSD calculations were performed on the Swiss-PDBViewer v4.1 16 and the analysis of the location of the mutations and image production was performed on the UCSF Chimera. 17 The SARS-CoV-2 NSP1 structure (PDB identification code: 7K7P), the rabbit 40S ribosome complex (7JQB), 18,19 and the Drosophila melanogaster 80S ribosome 20 (4V6W) were used as templates (Figure 1). After this initial modeling, fragment 3 (regions 128 to 144) was subjected to a loop refinement in the Modeller software's advanced routine.…”
Section: Methodsmentioning
confidence: 99%
“…An emerging infection is usually caused by the naive immunity of human beings encountering a novel pathogen arising from microbial mutation, vector-borne, or/and zoonotic transmission (Table 1) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Most of the common emerging infections are mediated by RNA viruses, which pose a higher rate of genetic mutation, sequence deletion, recombination, and reassortment of RNA virus codes (1,13).…”
Section: Evolution Of An Emerging Infection On An Imbalance Between Infection and Immunitymentioning
confidence: 99%
“…Most of the common emerging infections are mediated by RNA viruses, which pose a higher rate of genetic mutation, sequence deletion, recombination, and reassortment of RNA virus codes (1,13). As shown in Table 1, severe acute respiratory syndrome (SARS), avian flu, swine flu, and enterovirus 71 (EV71) are known to emerge from sequence mutation, deletion, recombination, and/or reassortment of RNA segments (1)(2)(3)(4)(5)(6). Vector-borne diseases such as yellow fever, dengue hemorrhagic fever, and West Nile virus encephalitis are transmitted by mosquitos (Table 1) and affected by weather, global warming, and herd immunity (5)(6)(7)(8)(9).…”
Section: Evolution Of An Emerging Infection On An Imbalance Between Infection and Immunitymentioning
confidence: 99%
“…Although several cryo-EM structures of nsp1, which suppress the innate immune function of the host, in a huge complex with human 40S ribosomal subunit have been published in PDB 59,60 , FMODB currently has only the calculated X-ray crystal structure of nsp1 alone (PDBID 7K7P, FMODBID: 5965Z) 61 , and the complex structure is under calculation. The structures of nsp2 (PDBID: 7MSW) and nsp14 (PDBID: 7DIY), which were published in PDB in May 2021, are currently under investigation.…”
Section: Other Sars-cov-2mentioning
confidence: 99%